2023
DOI: 10.1039/d2dt03764e
|View full text |Cite
|
Sign up to set email alerts
|

Near thermal, selective liberation of hydrogen from formic acid catalysed by copper hydride ate complexes

Abstract: Copper hydride ate complexes can effectively catalyse the selective decomposition of formic acid into carbon dioxide and hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…At last, in 2023, O’Hair and co-workers revealed that the mononuclear cuprate hydride anions [(X)­CuH] − (X = H – , O 2 CH – , BH 4 – , and CN – ) reacted in the gas phase with formic acid to release H 2 with the formation of the formate [(X)­Cu­(O 2 CH)] − compound. The latter decarboxylates readily via collision-induced dissociation to regenerate the initial copper hydride …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At last, in 2023, O’Hair and co-workers revealed that the mononuclear cuprate hydride anions [(X)­CuH] − (X = H – , O 2 CH – , BH 4 – , and CN – ) reacted in the gas phase with formic acid to release H 2 with the formation of the formate [(X)­Cu­(O 2 CH)] − compound. The latter decarboxylates readily via collision-induced dissociation to regenerate the initial copper hydride …”
Section: Resultsmentioning
confidence: 99%
“…The latter decarboxylates readily via collision-induced dissociation to regenerate the initial copper hydride. 78 The dynamic exchange process of 1 under CO 2 suggested that it could be a rare copper catalyst for the dehydrogenation of formic acid. We reasoned that if the hydride intermediate could trap gaseous CO 2 , it should also react quickly with the acid HCO 2 H, which is liquid and more abundant in solution than a gas (Scheme 3).…”
Section: Synthesis and Characterization Of [(Phen*)cu(κ 1 -O 2 Ch)] (1)mentioning
confidence: 99%
“…8 A range of charged metal hydride complexes have been reported to mediate the selective gas-phase decomposition of HCO 2 H into CO 2 and H 2 , and all follow a similar two-step formal catalytic cycle (cycle 1, Scheme 1B) with similar mechanistic features. 5,6,9 In step one, the coordinated hydride undergoes an ion-molecule reaction with formic acid to liberate hydrogen in which the coordinated hydride is replaced by a coordinated formate. Step two involves decarboxylation of the coordinated formate – here the coordinated formate acts as a hydride donor (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%